2013
DOI: 10.1002/pmic.201200179
|View full text |Cite
|
Sign up to set email alerts
|

Differential secretome analysis of cancer‐associated fibroblasts and bone marrow‐derived precursors to identify microenvironmental regulators of colon cancer progression

Abstract: The identification of cancer-associated fibroblast (CAF)-derived proteins that mediate interactions between the tumor stroma and cancer cells is a crucial step toward the discovery of new molecular targets for therapy or molecular signatures that improve tumor classification and predict clinical outcome. CAF are α-smooth muscle actin positive, representing a myofibroblast phenotype that may differentiate from multiple precursor cells, including bone marrow-derived mesenchymal stem cells (MSC). Transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 43 publications
2
65
0
Order By: Relevance
“…This was previously described in other studies that investigated CAFs derived from other tumors [18,19,22,52]. In a recent study, Rasanen and collaborators [20] characterized the secretomes of E-cadherin low mesenchymal-like subpopulations of OSCCs, which resembled that of CAFs, and revealed upregulation of several proteins involved in organization of the extracellular matrix, such as multiple types of collagen.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This was previously described in other studies that investigated CAFs derived from other tumors [18,19,22,52]. In a recent study, Rasanen and collaborators [20] characterized the secretomes of E-cadherin low mesenchymal-like subpopulations of OSCCs, which resembled that of CAFs, and revealed upregulation of several proteins involved in organization of the extracellular matrix, such as multiple types of collagen.…”
Section: Discussionmentioning
confidence: 80%
“…Identifying proteins synthesized by CAFs is crucial for a better understanding of the biological events associated with oral tumorigenesis and for the discovery of new tumor biomarkers, enabling, for example, discrimination of patients at high and low risk of developing metastasis and allowing for more individualized treatment. Previous studies have already identified proteins secreted by CAFs in colorectal [18,19], head and neck cancer [20], and nasopharyngeal cancer [21]. In a previous study, we demonstrated that CAFs promote tumorigenesis of oral tongue SCC cell lines via secretion of high levels of activin A, a member of the transforming growth factor-β superfamily of proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comparative transcriptomic analysis of paired CAFs and normal fibroblasts (NF) identified 108 genes, mostly downregulated (17). In a proteomic study, colon cancer CAFs were compared with bone marrow precursors to identify tenascin C, ED-A fibronectin, and SDF-1 as deregulated in CAFs (18). Recently, we used a murine model of sporadic colon cancer based on azoxymethane/dextran sodium sulfate to optimize fibroblast purification and characterize alterations in murine CAFs (19).…”
Section: Introductionmentioning
confidence: 99%
“…Human CAF were isolated from a colorectal adenocarcinoma resection specimen obtained in accordance with the local ethics committee (Ghent University Hospital) described by De Boeck et al [9,14]. In sort, tissue fragments were cut in small pieces and transferred into a 6-well late fetal FBS.…”
Section: Cell Linesmentioning
confidence: 99%
“…CAFs secrete a range of ECM proteins (e.g. type I collagen, tenascine C) creating a receptive adhesive environment for peritoneal implant formation [9].…”
Section: Introductionmentioning
confidence: 99%